Integrated Reporting, Quality of Management, and Financial Performance. Issue 1 (March 2014) - Churet, Cécile; Eccles, Robert G.
<x xml:space="preserve">Abstract</x> Interest in integrated reporting continues to grow as its proponents cite a number of significant benefits to both companies and investors. But given the still‐early stages of development of this new management practice and the relative paucity of data, establishing empirical confirmation of these claims is difficult. Using RobecomSAM's proprietary database of over 2, 000 companies surveyed during its annual Corporate Sustainability Assessment (CSA), the authors discuss the extent and recent growth of integrated reporting, and its likely effects on important indicators of both ESG quality of management and financial performance. The authors begin by reporting that although only 12% of the companies in the survey dataset practiced some form of integrated reporting in 2012, that number represented a 50% increase from 2011. The authors also report a strong relationship between integrated reporting and ESG quality of management, which some studies suggest has become a useful indicator of the overall effectiveness of management in creating value over the long term. This relationship is particularly strong in certain sectors, notably healthcare. At the same time, the authors find a relationship between integrated reporting and financial performance for two sectors—healthcare and information technology—though not for the population as a whole. The authors suggest that this apparent lack of effect may be attributable to a time lag between integrated reporting's contribution to better ESG quality of management, and the eventual reflection of such management in financial performance.